2022
DOI: 10.1001/jamaneurol.2022.0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Rates of Recurrent Ischemic Stroke Among Young Adults With Embolic Stroke of Undetermined Source

Abstract: IMPORTANCE Cryptogenic strokes constitute approximately 40% of ischemic strokes in young adults, and most meet criteria for the embolic stroke of undetermined source (ESUS). Two randomized clinical trials, NAVIGATE ESUS and RESPECT ESUS, showed a high rate of stroke recurrence in older adults with ESUS but the prognosis and prognostic factors among younger individuals with ESUS is uncertain. OBJECTIVE To determine rates of and factors associated with recurrent ischemic stroke and death and new-onset atrial fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…The rate of detected AF was low and did not differ between female and male AIS patients in our cohort. This is consistent with data from the Young ESUS longitudinal Cohort Study including 535 young adult patients with embolic stroke of undetermined source which also reported low rates of newly detected AF (2.8%) [ 6 ]. Arterial dissection was detected in 17.8% of our patient cohort, and did not significantly differ between young female and male AIS patients.…”
Section: Discussionsupporting
confidence: 90%
“…The rate of detected AF was low and did not differ between female and male AIS patients in our cohort. This is consistent with data from the Young ESUS longitudinal Cohort Study including 535 young adult patients with embolic stroke of undetermined source which also reported low rates of newly detected AF (2.8%) [ 6 ]. Arterial dissection was detected in 17.8% of our patient cohort, and did not significantly differ between young female and male AIS patients.…”
Section: Discussionsupporting
confidence: 90%
“…Particularly in patients poststroke of undetermined source based on the TOAST criteria, the CRYSTAL AF study identified 12.4% AF at 12 months in patients randomized to receive an ICM 5 . In contrast, patients aged younger than 50 years with ESUS had a significantly lower incidence of AF, even when equipped with ICM 24 . More recently, the FIND‐AF‐randomized trial used three times 10‐day Holter recordings in patients after an ischemic stroke and detected AF in 13.5% after 6 months 25 .…”
Section: Discussionmentioning
confidence: 99%
“…5 In contrast, patients aged younger than 50 years with ESUS had a significantly lower incidence of AF, even when equipped with ICM. 24 More recently, the FIND-AF-randomized trial used three times 10-day Holter recordings in patients after an ischemic stroke and detected AF in 13.5% after 6 months. 25 In our current investigation, the overall cumulative incidence of AF was 9.1% after 6 months and 12.5% after 12 months follow-up, and it was 10.6% (6 months) and 14.5% (12 months) when restricted to those patients equipped with an ICM.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, too, is an important contributor to outcome, as smoking was recently associated with a higher 3 month NIHSS in a study in China [19]. Cryptogenic stroke has been associated with higher rates of recurrence in young adults than those with other causes [20,21 ]. Patent foramen ovale closure, previously considered controversial, has been recently shown to have clear benefit in stroke prevention in young adults without an alternative explanation for stroke [22].…”
Section: Importance Of Risk Factorsmentioning
confidence: 99%